The virtual fields method - Syed Muhammad, Kashif (IIUM Press, 2011)
This chapter discusses virtual fields method which is used for characterization of composite or anisotropic material with the use of full field heterogeneous deformation data. The method has shown very promising results when used for identification of materials constitutive properties and a set of full field data. This chapter discusses the basic working principle of the method and then it discusses the various developments made to its further enrichment. For the case of composite plates the method has been tested in various conditions from static to dynamic, from linear to non-linear and also it has been applied to the case of damage characterization.